2010
DOI: 10.5194/angeo-28-2007-2010
|View full text |Cite
|
Sign up to set email alerts
|

Tropical connection to the polar stratospheric sudden warming through quasi 16-day planetary wave

Abstract: Abstract. The Planetary Waves (PWs) are believed to have significant role in generating the wintertime warming over the polar stratosphere, known as Stratospheric Sudden Warming (SSW). However, the origin, characteristics and evolution of these waves are still speculative. The possibility that the PWs over the polar stratosphere, which play an important role in the generation of SSW, could also have contribution from the tropics has been indicated through many numerical simulations in the past, but due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…During the easterly phase of the QBO, there is propagation of these planetary waves (originating in the high latitudes) in the stratosphere across the equator, while in the westerly phase of the QBO, the planetary waves break at ∼ 20-25 • N and there is no propagation across the equator. Hence a spectral analysis of winds at the low latitudes during the easterly phase of the QBO could indicate the presence of planetary waves with periods comparable to the ones causing the onset of the SSW as in [2005][2006] and reported on by Vineeth et al (2010). However, our analysis indicates that the planetary wave propagation is equatorward from the mid-high latitudes during the SSW events and gives no indication of poleward propagation of planetary waves in the tropics as reported by Vineeth et al (2010).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the easterly phase of the QBO, there is propagation of these planetary waves (originating in the high latitudes) in the stratosphere across the equator, while in the westerly phase of the QBO, the planetary waves break at ∼ 20-25 • N and there is no propagation across the equator. Hence a spectral analysis of winds at the low latitudes during the easterly phase of the QBO could indicate the presence of planetary waves with periods comparable to the ones causing the onset of the SSW as in [2005][2006] and reported on by Vineeth et al (2010). However, our analysis indicates that the planetary wave propagation is equatorward from the mid-high latitudes during the SSW events and gives no indication of poleward propagation of planetary waves in the tropics as reported by Vineeth et al (2010).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Hence a spectral analysis of winds at the low latitudes during the easterly phase of the QBO could indicate the presence of planetary waves with periods comparable to the ones causing the onset of the SSW as in [2005][2006] and reported on by Vineeth et al (2010). However, our analysis indicates that the planetary wave propagation is equatorward from the mid-high latitudes during the SSW events and gives no indication of poleward propagation of planetary waves in the tropics as reported by Vineeth et al (2010). The effects of the planetary wave propagation across the tropical stratosphere during the easterly phase of the QBO have been reported during the early winter months of November and December (Ortland, 1997;O'Sullvan, 1997).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fagundes et al (2005) A series of recent reports concerning ionospheric perturbations associated with lower atmospheric forcing have focused on sudden stratospheric warming (SSW). These reports mainly discussed the features of the ionospheric variation in low-latitude region, the possible connections between the state of the atmosphere at low latitude and high latitude, and the possible connections between the ionosphere and MLT region related to SSW Goncharenko et al, 2010a, b;Mukhtarov et al, 2010;Pedatella and Forbes, 2009;Vineeth et al, 2007Vineeth et al, , 2010. Using the global reanalysis data of atmospheric temperature and wind provided by the National Centers for Environmental Prediction (NCEP) and National Center for Atmospheric Research (NCAR), Vineeth et al (2010) found an enhanced planetary wave (PW) activity of quasi-16-day periodicity in the stratosphere propagating from the Equator to the North Pole during several SSW years.…”
Section: Introductionmentioning
confidence: 99%
“…Fritz and Soules (1970) first revealed the lower temperature in the tropical stratosphere during an SSW event by satellite data. Several subsequent studies, both theoretical and observational, investigated the relationship between the tropical region and the SSW events (Garcia, 1987;Holton et al, 1995;Plumb and Eluszkiewicz, 1999;Randel et al, 2002;Vineeth et al, 2010;Yoshida and Yamazaki, 2011). These studies stated that the meridional circulation driven by the transient planetary wave forcing associated with polar SSWs can induce upwelling in the tropical region, in turn produce cooling in the stratosphere and upper troposphere in the tropical region during SSW events.…”
Section: Introductionmentioning
confidence: 99%